2016
DOI: 10.2147/ott.s97644
|View full text |Cite
|
Sign up to set email alerts
|

New developments in the management of non-small-cell lung cancer, focus on rociletinib: what went wrong?

Abstract: Recently, the development of the third-generation epidermal growth factor receptor-small molecule inhibitor (EGFR-TKI) rociletinib had failed. In this review, the wide-ranging aspects of the evolution of EGFR-TKIs were collected, with a special focus on rociletinib. The influence of different oncogenic mutations on EGFR activity was also discussed. Resistance to the first (erlotinib, gefitinib)- and second (afatinib)-generation EGFR-TKIs provided the rationale behind the development of the third-generation inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 56 publications
2
26
0
Order By: Relevance
“…However, additional development costs and risks (eg, withdrawal from the market) remain. 36 High-level timelines have been previously published for USA marketing approvals, 4 and were found to be in line with the findings of the present analysis. Prior to this, it was reported that an average of 12 years was necessary for an experimental drug to progress from bench to market.…”
Section: Discussionsupporting
confidence: 91%
“…However, additional development costs and risks (eg, withdrawal from the market) remain. 36 High-level timelines have been previously published for USA marketing approvals, 4 and were found to be in line with the findings of the present analysis. Prior to this, it was reported that an average of 12 years was necessary for an experimental drug to progress from bench to market.…”
Section: Discussionsupporting
confidence: 91%
“…Small molecule inhibitors of EGFR such as erlotinib and gefitinib, are only active in adenocarcinoma of non-small cell lung cancer when the tumor has activating mutations, making the tumor cell dependent on (or addicted to) EGFR signaling. Additional mutations (e.g., T790M) lead to resistance, but these cells are sensitive to the 3rd generation of EGFR inhibitors [13] . From these data it should be noted, that dependent on the target a high expression (or mutated enzyme) can lead to either resistance or increased sensitivity.…”
Section: What Is Special In the First Issue?mentioning
confidence: 99%
“…A decreased uptake or increased efflux may limit the cellular drug accumulation, and the efficacy of these drugs [5]. Moreover, inhibition may be reversible or irreversible; especially novel third or fourth generation TKIs display irreversible enzyme inhibition [6]. Recently we demonstrated that sunitinib, an inhibitor of the Vascular endothelial growth factor receptor (VEGFR) accumulates in lysosomes [7], while preliminary experiments demonstrated a similar distribution for crizotinib, an ALK-EML4 and cMET inhibitor [5].…”
Section: Introductionmentioning
confidence: 99%